Peran Stimulus Lingkungan terhadap Mekanisme Biologi Pembelajaran : Kajian Neurofisiologis pada Peserta Didik - Hidayat, Doni; Sartika, Fikri (Lembaga Publikasi Ilmiah Nusantara, 2025)
The validation results of the project-based learning model integrated with green economy concepts indicate that the developed model falls into the highly valid category based on expert evaluations. The validation process involved three experts from relevant fields who assessed five main aspects: model construction, clarity of learning syntax, content suitability, integration of green economy principles, and the model’s potential to enhance sustainability literacy. The overall mean score obtained was 3.62 out of a maximum score of 4.00, demonstrating a very high level of validity. Quantitative findings were reinforced by qualitative feedback from experts, who highlighted the systematic structure of the learning stages, particularly in the problem exploration and project design phases. The clarity of the project-based learning syntax was rated very highly, especially in the phase that encourages students to investigate and analyze real-world green economy issues. Although the integration of green economy concepts was considered appropriate, experts suggested strengthening the use of empirical data and balancing economic, social, and environmental sustainability indicators. Overall, the validation results suggest that the proposed learning model is theoretically sound and feasible for implementation in economics education. This model has strong potential to improve students’ sustainability literacy by fostering knowledge, skills, and attitudes aligned with sustainable development principles and can serve as a foundation for further studies on practicality and effectiveness.